INTEGRAL CRIME CONTROL IN THE PERSPECTIVE OF CRIMINAL POLITICS - Endah Sriwati (Journal Philosophy of Law, 2023)
The research in this paper aims to find out how crime prevention can be carried out through an integral criminal political approach and whether the handling of crime is as expected. This research is normative by using statutory and conceptual approaches and expert opinions. Crime can be seen from two aspects, namely, from a social perspective. Crime is all kinds of actions and actions that can cause harm, disturb peace and balance, and violate societal norms. Meanwhile, from a formal point of view, crime is an act that violates the law or law, and the perpetrators can be subject to sanctions in the form of imprisonment, fines, and others. The study concluded that integral crime prevention through a criminal political approach could be carried out in a penal and non-penal manner. Through an approach with penal means that focuses more on the repressive nature (suppression/eradication) after the crime has occurred. Meanwhile, non-penal means focusing more on preventive nature (prevention/control) before a crime occurs. Penal means can be carried out through the criminal justice system, namely by applying criminal sanctions as stipulated in the Criminal Code, in particular Article 10 of the Criminal Code, which regulates the types of punishment. In addition, criminal sanctions can be used through other laws and regulations that regulate criminal provisions (Article 103 of the Criminal Code). Crime prevention, through an integral political approach with penal and non-penal means, is intended to improve the perpetrators of crimes, prevent crimes from occurring so that victims do not arise, and, more importantly, in the framework of social defense and social welfare.